2017
DOI: 10.1111/bcp.13237
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CES1 genotypes on the pharmacokinetics of methylphenidate in healthy Danish subjects

Abstract: The 143E allele resulted in an increased AUC, suggesting a significantly decreased CES1 enzyme activity. Surprisingly, this was also the case in subjects with homozygous duplication of CES1, perhaps reflecting an undiscovered mutation affecting the activity of the enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 31 publications
3
46
1
Order By: Relevance
“…In terms of the CES1 143E allele, we found no pharmacokinetic impact on the metabolism of enalapril. This is in contrast to our MPH study, in which a markedly (149%) and highly significant increase in d ‐MPH AUC was found compared to the control group indicating decreased metabolizing capacity . In a recent human study, Tarkiainen et al .…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of the CES1 143E allele, we found no pharmacokinetic impact on the metabolism of enalapril. This is in contrast to our MPH study, in which a markedly (149%) and highly significant increase in d ‐MPH AUC was found compared to the control group indicating decreased metabolizing capacity . In a recent human study, Tarkiainen et al .…”
Section: Discussioncontrasting
confidence: 99%
“…All volunteers were informed about trial objectives and potential risks prior to their participation, and an informed consent form was signed by each subject. Detailed inclusion criteria have been described elsewhere . The study was conducted in accordance with the Basic & Clinical Pharmacology & Toxicology policy for experimental and clinical studies …”
Section: Methodsmentioning
confidence: 99%
“…Lower limit of quantification was 0.205 ng/mL for the MPH isomers and 2.05 ng/mL for the RA isomers. The procedure has been described more detailed elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On testing correlations between CES1 genotype and PK, significance was mostly seen in the comparison between the normal genotype (group 1) and the group with the rs71647871 143E allele ( n = 6) with a higher AUC of d‐MPH, half‐life of d‐MPH, and C max of d‐MPH in the latter of these two groups ( Table ). Detailed analysis of the genotype/PK comparisons shown in Table have been previously reported using a slightly different statistical approach, which involved application of the Kruskal‐Wallis test …”
Section: Resultsmentioning
confidence: 99%